2007
DOI: 10.1111/j.1365-2850.2007.01058.x
|View full text |Cite
|
Sign up to set email alerts
|

Bordering on insanity: misnomer, reviewing the case of condemned women

Abstract: In the UK, there have been calls to develop gendered specific mental health services for women in an attempt to ensure privacy and dignity are achieved as and when women come into contact with services. This is a largely rhetorical policy objective. There are more fundamental factors affecting women's experience of mental health services that need addressing. This paper explores these issues in the context of mental health care for women who have been 'given' the diagnosis of borderline personality disorder (B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 55 publications
0
7
0
Order By: Relevance
“…Five common themes were identified as the major barriers to one‐to‐one care: administrative duties, understanding one‐to‐one sessions, control over workload, staff needs, and ward culture (Edwards ). Ward culture and understanding one‐to‐one care are interesting in terms of there being a common belief among mental health practitioners that those who experience serious mental illness are not capable of engaging in therapeutic relationships (Warne & McAndrew ). However, this is challenged by Bentall et al .…”
Section: Measuring the Therapeutic Relationshipmentioning
confidence: 99%
“…Five common themes were identified as the major barriers to one‐to‐one care: administrative duties, understanding one‐to‐one sessions, control over workload, staff needs, and ward culture (Edwards ). Ward culture and understanding one‐to‐one care are interesting in terms of there being a common belief among mental health practitioners that those who experience serious mental illness are not capable of engaging in therapeutic relationships (Warne & McAndrew ). However, this is challenged by Bentall et al .…”
Section: Measuring the Therapeutic Relationshipmentioning
confidence: 99%
“…The conclusions drawn in these studies were that psychiatric nurses perceived those with BPD as 'bad', and other patients as 'ill' (Gallop et al 1989, Fraser & Gallop 1993, Deans & Meocevic 2006, Thornicroft 2007. It is believed by many theorists that the diagnosis of BPD itself has become a pejorative 'label' ascribed to those patients (generally female) who the clinician does not particularly like, and that the use of the term itself needs to be seriously questioned (Fraser & Gallop 1993, Warne & McAndrew 2007. These attitudes can even be taken to the point of explicit segregation, where diagnoses of BPD have become exclusion criteria for some agencies' or programmes' provision of care services (Thornicroft 2007).…”
Section: B Psychiatric Nurses' Attitudesmentioning
confidence: 99%
“…It has been argued that the psychiatric model provides nurses with limited treatment options and facilitates feelings of inadequacy, anger and resentment towards clients who have received this diagnosis (Nehls 1998; Krawitz and Watson 1999; Crowe 2000b). Warne and McAndrew (2007) have suggested that categorical labels evoke a wide range of conscious and unconscious responses and that mental health nurses need to recognise the defence mechanisms involved. Feely, Sines and Long (2007) has proposed that diagnostic manuals, which act as points of reference for professionals, encourage healthcare staff to proffer medically related diagnoses and mental health nursing has contributed actively to this process.…”
Section: Nursing Concernsmentioning
confidence: 99%